Rapid detection of H and R Panton-Valentine leukocidin isoforms in Staphylococcus aureus by high-resolution melting analysis - Tong, S.; Lilliebridge, R.; Holt, D.; Coombs, Geoffrey; Currie, B.; Giffard, P. (Elsevier, 2010)
We designed a single-step, closed-tube, real-time polymerase chain reaction and high-resolution melting assay to simultaneously detect the presence of the Panton-Valentine leukocidin gene and discriminate histidine and arginine isoforms. Of 223 Staphylococcus aureus isolates from northern Australia, isoforms clustered by clonal complex (CC). All CC93 isolates harbored the arginine isoform. © 2010.